2000
DOI: 10.1097/00001756-200012180-00014
|View full text |Cite
|
Sign up to set email alerts
|

The use of a recombinant lentiviral vector for ex vivo gene transfer into the rat CNS

Abstract: A major obstacle in ex vivo gene transfer has been the loss of transgene expression soon after implantation of the grafted transduced cells. Recently, a lentiviral vector system has been developed which has proven to express high levels of transgenes in vivo after direct injection into the tissue. In this study, we have investigated the use of such a vector for ex vivo gene transfer to the brain. A number of neural cell types were found to be permissive to transduction by the lentiviral vector in vitro and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 7 publications
6
48
0
Order By: Relevance
“…For instance, it has recently been shown, that ex vivo gene transfer of LV vector transduced polyclonal HiB5 cells to neonatal rats could promote sustained transgene expression (8 weeks), though expression levels were considerably reduced in most cells. 14 The same study also showed that the time aspect of downregulation apparently is cell type-related, since in vivo transgene expression was found to vary between cells of different type transduced with the same LV reporter construct and grafted to the rat brain.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, it has recently been shown, that ex vivo gene transfer of LV vector transduced polyclonal HiB5 cells to neonatal rats could promote sustained transgene expression (8 weeks), though expression levels were considerably reduced in most cells. 14 The same study also showed that the time aspect of downregulation apparently is cell type-related, since in vivo transgene expression was found to vary between cells of different type transduced with the same LV reporter construct and grafted to the rat brain.…”
Section: Discussionmentioning
confidence: 87%
“…Previous in vivo studies have shown that the immortalized HiB5 cell line survive grafting very well, remain stable for at least 6 months and become structurally integrated within an area surrounding the implantation site. [13][14][15] The in vivo expression stability of UbC and CMV constitutive promoters was compared by transplanting HiB5 cells stably expressing EGFP from the UbC promoter or the CMV promoter to the striatum. Expression of EGFP from both promoters was significantly down-regulated over 21 days ( Figure 2) and no difference in expression stability was seen between cells expressing EGFP under the CMV or UbC promoters, respectively (data from CMV-EGFP not shown).…”
Section: Influence Of Promoter On Expression Stability: Comparison Ofmentioning
confidence: 99%
“…While the results described above concern the haematopoietic system, only a limited number of studies in solid tissue show stable modification of mature cells by transduction of progenitor cells [17][18][19]. However, in these reports, only constitutive promoters were used, resulting in an expression of the transgene without cell type restriction.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] An increasing number of studies report efficient ex vivo gene transfer into cells prior to transplantation, for example, transduction of haematopoietic stem cells with subsequent repopularization of irradiated NOD/SCID mice bone marrow 7 or CNS cells. 8 Furthermore, lentiviral ex vivo gene transfer is not only performed for therapeutic gene transfer but also to label cells with suitable reporter genes, such as enhanced green fluorescent protein (eGFP), for example, to explore differentiation of stem or progenitor cells after cell transplantation or co-cultivation with other cell types. [8][9][10][11][12] Further incubation of transduced cells prior to transplantation or co-cultivation is often inconvenient and cells are therefore washed several times to remove surplus viral particles.…”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, lentiviral ex vivo gene transfer is not only performed for therapeutic gene transfer but also to label cells with suitable reporter genes, such as enhanced green fluorescent protein (eGFP), for example, to explore differentiation of stem or progenitor cells after cell transplantation or co-cultivation with other cell types. [8][9][10][11][12] Further incubation of transduced cells prior to transplantation or co-cultivation is often inconvenient and cells are therefore washed several times to remove surplus viral particles. In other cases, further cultivation is in fact impossible, as certain cell types require almost immediate transplantation after transduction to prevent cell death, de-differentiation, differentiation or adhesion.…”
Section: Introductionmentioning
confidence: 99%